Kim był książę „Pomorza”, którego pokonał węgierski książę Béla? - Madeja, Karolina (Średniowiecze Polskie i Powszechne, 2019)
Hungarian chronicles contain accounts regarding a duel between a Duke of Pomerania and the Hungarian Prince Béla, who, alongside his brothers, was at the time a guest of the Polish King Mieszko II. Polish historiography questions the identity of the Polish ruler, situa- ting the events during the reign of Casimir I the Restorer, while Hungarian historiography doubts the opponent’s connections with Pomerania or even the very fact of the duel. Thus, the following article shows that, in the context of anachronistic political data included in the Hun‑ garian sources, the Pomeranian ancestry of the defeated duke is not sufficiently substantiated and cannot be the basis of a chronological correction. On the other hand, when it comes to the identity of the Polish ruler, a careful analysis of both the relationship between the Piast and the Arpad dynasty, as well as the last years of the rule of Mieszko II substantiates the hypothesis that it was indeed him who took in the exiled princes. The information included in the Hun‑ garian chronicles possibly describes the situation after the Congress of Merseburg (1032): the dethroning of Theoderick, which could occur as a result of a trial by combat, practiced at that time in this cultural sphere. Moreover, if one were to treat the mention of the Duke of Pomera‑ nia as credible, it could be regarded as clue regarding Theoderick’s province, which presumably could be Pomerania.